PENGARUH HARGA, PROMOSI DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN CAT SEMPROT SAMURAI PADA PT. WSTANDARD MEGA ABADI - Pardede, Sonia Thresia; Sa, Kenny Mok; Situmeang, Rosinta Romauli (2020)
This research was conducted to analyze and examine the effect of price, promotion, and facilities on purchasing decisions of Samurai spray paint at PT. Wstandard Mega Abadi. The total population is 152 customers, using the Slovin formula, a sample of 110 customers is obtained. The sampling technique used simple random sampling. Data_analysis techniques used are classical assumptions, multiple linear regression, and hypothesis testing. The hypothesis partially and simultaneously obtained that the variable price, promotion. and facilities partially and simultaneously have a positive and significant effect on the decision to purchase Samurai spray paint by using a comparison of the value of tcount > ttable and Fcount > Ftable.